A crystallographically characterized salt of self-generated N-protonated tetraethylurea. Issue 7 (8th December 2014) - Bortoluzzi, Marco; Marchetti, Fabio; Pampaloni, Guido; Zacchini, Stefano
Abstract : The first crystallographically characterized N -protonated urea (1, 1, 3, 3-tetraethylurea, teu) was obtained by a WCl6 -directed electron transfer/C–H activation process. Abstract : The reaction of 1, 1, 3, 3-tetraethylurea (teu) with WCl6 in dichloromethane afforded [teuH][WCl6 ], 1, in 50–60% yield. The X-ray structure determined for1 includes the first example of crystallographic characterization of a N -protonated urea. According to spectroscopic and DFT outcomes, the formation of1 is the result of an electron transfer/C–H activation process.